A Characterization of 4-Centralizer Groups. (26th December 2013) - Dutta, Jutirekha
Abstract : A finite or infinite group is called an n -centralizer group if it has n numbers of distinct centralizers. In this paper, we prove that a finite or infinite group G is a 4-centralizer group if and only if G / Z ( G ) is isomorphic to C 2 × C 2 . This extends a result of Belcastro and Sherman.